Pytim: A python package for the interfacial analysis of molecular simulations - Sega, Marcello; Hantal, György; Fábián, Balázs; Jedlovszky, Pál (Journal of computational chemistry, 2018)
Pytim is a versatile python framework for the analysis of interfacial properties in molecular simulations. The code implements several algorithms for the identification of instantaneous interfaces of arbitrary shape, and analysis tools written specifically for the study of interfacial properties, such as intrinsic profiles. The code is written in the python language, and makes use of the numpy and scipy packages to deliver high computational performances. Pytim relies on the MDAnalysis library to analyze the trajectory file formats of popular simulation packages such as gromacs, charmm, namd, lammps or Amber, and can be used to steer OpenMM simulations. Pytim can write information about surfaces and surface atomic layers to vtk, cube, and pdb files for easy visualization. The classes of Pytim can be easily customized and extended to include new interfacial algorithms or analysis tools. The code is available as open source and is free of charge. © 2018 The Authors. Journal of Computational Chemistry published by Wiley Periodicals, Inc Determining the interface between fluid phases described at the molecular level is a complicated problem with no unique solution. The experimental nature of many of the available codes represents a severe limitation to the wider diffusion of such kind of analysis. The authors present a python package that implements several algorithms for the analysis of intrinsic interfaces, allows to analyze the most popular trajectory formats with minimal scripting efforts.